2006
DOI: 10.1590/s1516-14392006000300007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the corrosion resistance of DIN W. Nr. 1.4970 (15%Cr-15%Ni-1.2%Mo-Ti) and ASTM F-138 (17%Cr-13%Ni-2.5%Mo) austenitic stainless steels for biomedical applications

Abstract: The resistance to localised corrosion of the full austenitic 15%Cr-15%Ni-1.2%Mo titanium stabilized stainless steel (DIN W. Nr. 1.4970) was investigated by electrochemical methods including electrochemical impedance spectroscopy (EIS), potentiodynamic polarization and potentiostatic polarization measurements in a phosphatebuffered solution (PBS). The low carbon and non-stabilized austenitic stainless steel, AISI 316L (ASTM F-138), widely used for surgical implants, was also tested for comparison. The tests wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The dynamic features of oxide film are the key factors of high corrosion resistance of stainless steels in corrosive environments. In addition, the presence of Molybdenum in 316L stainless steel increases the resistance to pitting corrosion in saline environments [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic features of oxide film are the key factors of high corrosion resistance of stainless steels in corrosive environments. In addition, the presence of Molybdenum in 316L stainless steel increases the resistance to pitting corrosion in saline environments [7].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these problems, stainless steel implants are still currently used due to a combination of corrosion resistance, mechanical strength, ductility, toughness and easy fabrication at low cost [7]. Survey of failed stainless implants indicates that majority of failure in 316L SS implants is because of pitting or crevice corrosion, fatigue and wear [5,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Ti and Ti alloys are by far the most used materials for body implants; however, their excessive prices make them unaffordable to the health public system of underdeveloped countries. Thus researches on biocompatibility and corrosion resistance on simulating body fluid solutions of less expensive materials are under way in many countries [1,2]. Milosev and Strehblow [3] studied the corrosion behavior of stainless steels in a physiological solution and concluded that the properties of the passive layer, account for the corrosion resistance of orthopedic implants produced with these materials.…”
Section: Introductionmentioning
confidence: 99%
“…Once more, a 60 min time gap was applied between the two polarizations. Each polarization test was terminated when the value of corrosion current density reached 2 × 10 −3 A/cm −2 , which ensured that the material was located in a transpassive state and the surface was actively corroded [11].…”
Section: Commented [M8]: Is the Underline Necessary?mentioning
confidence: 99%